ASSET MEASUREMENT AND THE NEED FOR AN INCOME THEORY - Abuzrida, Mokhtar (Dirasat in Economics and Business, 1972)
The problem of income determination has been the main concern of accounting measurement in business enterprises. This interest in enterprises income has influenced all attempts in the accounting literature to develop a theory on which accounting measurement can be based. Edwards and Bell wrote: the need for development of a rigorous concept of business income, one which rests on sound theoretical understandings yet is measured in practice, is indisputable. Business income is one of the key elements of information upon which the functioning of a private, free enterprise economy depends. 1